Pre‐glycation impairs gelation of high concentration collagen solutions. Issue 12 (11th August 2022) - Diamantides, Nicole; Slyker, Leigh; Martin, Sara; Rodriguez, Marcos R.; Bonassar, Lawrence J.
Abstract: There remains a need for stiffer collagen hydrogels for tissue engineering and disease modeling applications. Pre‐glycation, or glycation of collagen in solution prior to gelation, has been shown to increase the mechanics of collagen hydrogels while maintaining high viability of encapsulated cells. The stiffness of glycated collagen gels can be increased by increasing the collagen concentration, sugar concentration, and glycation time. However, previous studies on pre‐glycation of collagen have used low collagen concentrations and/or low sugar concentrations and have not investigated the effect of glycation time. Therefore, the objective of this study was to determine the effects of pre‐glycation with high sugar concentrations (up to 500 mM) and extended glycation times (up to 21 days) on high concentration collagen (8 mg/ml). The addition of sugar to the collagen and the formation of advanced glycation end products (AGEs) were quantified. The ability to gel successfully and rheological properties were determined and correlated with biochemical characterizations. Successful collagen gelation and rheological properties of pre‐glycated collagen were found to be strongly dependent on the ratio of added sugars to added AGEs with high ratios impairing gelation and low ratios resulting in optimal storage moduli. There is likely a competing effect during pre‐glycation of the formation of AGEs resulting in crosslinking of collagen and the formation of Amadori intermediates acting to increase collagen solubility. Overall, this study shows that collagen glycation can be optimized by increasing the formation of AGEs while maintaining a low ratio of added sugar to added AGEs.